2021
DOI: 10.1111/bjh.17510
|View full text |Cite
|
Sign up to set email alerts
|

Platelet autoantibody specificity and response to rhTPO treatment in patients with primary immune thrombocytopenia

Abstract: Summary This retrospective study aimed to evaluate the relationship between plasma autoantibody species and rhTPO response in adult ITP patients who failed the first‐line treatments. Plasma anti‐glycoprotein (GP) IIb/IIIa and anti‐GPIb/IX autoantibodies were detected in 47·2% and 40·6% of the 123 patients, respectively. Overall response rate to rhTPO treatment in patients without anti‐GPIb/IX autoantibodies was significantly higher than patients with anti‐GPIb/IX autoantibodies (82·2% vs. 60·0%, P = 0·006). By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Some biomarkers might be predictive factors for the responses of TPO‐RAs. The presence of anti‐GPIb/IX autoantibodies might indicate poor response to rhTPO treatment in ITP patients 72 . Moreover, the anti‐c‐Mpl antibody might also represent an indicator of poor prognosis and could be a potential therapeutic target in ITP 73 …”
Section: Discussionmentioning
confidence: 99%
“…Some biomarkers might be predictive factors for the responses of TPO‐RAs. The presence of anti‐GPIb/IX autoantibodies might indicate poor response to rhTPO treatment in ITP patients 72 . Moreover, the anti‐c‐Mpl antibody might also represent an indicator of poor prognosis and could be a potential therapeutic target in ITP 73 …”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10-20% of patients are relatively unresponsive to IVIG, particularly those with platelet autoantibodies directed against GP Ib/IX. Nevertheless, a trial of IVIG is justified in these, and other patients whose severe bleeding is uncontrolled by other measures [47].…”
Section: Emergency Treatment With Ivigmentioning
confidence: 99%
“…rhTPO is a full-length glycosylated TPO, whose bind site is similar to the endogenous TPO. 33 , 34 The median time to response of rhTPO is 4 days, 35 shorter than other treatments and suitable for the emergency treatment of ITP. 34 , 36 In our study, rhTPO plus dexamethasone showed the highest early response.…”
Section: Discussionmentioning
confidence: 99%